2022
DOI: 10.3389/fpubh.2022.972249
|View full text |Cite
|
Sign up to set email alerts
|

Head and face anthropometric study for respirators in the multi-ethnic Asian population of Malaysia

Abstract: BackgroundExisting anthropometric studies for respirator designs are based on the head and facial dimensions of Americans and Chinese nationals, with no studies for multi-ethnic countries like Malaysia. This study aimed to create head and facial morphological database for Malaysia, specifically to identify morphological differences between genders, ethnicities, and birthplaces, as well as predictors of the dimensions.DesignA cross-sectional study.SettingMalaysia.ParticipantsA nation-wide cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Following that, a bivariate RFTP was divided into ten size cells using the method described by Zhuang et al, and the cell boundaries were then adjusted so that the population can be distributed as uniformly as possible among cells (1). In this study, these procedures were followed for the development of new bivariate RFTP based on the results of our anthropometric survey (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following that, a bivariate RFTP was divided into ten size cells using the method described by Zhuang et al, and the cell boundaries were then adjusted so that the population can be distributed as uniformly as possible among cells (1). In this study, these procedures were followed for the development of new bivariate RFTP based on the results of our anthropometric survey (10).…”
Section: Discussionmentioning
confidence: 99%
“…A population-based cross-sectional study was conducted across the country using complex sample design that included direct measurement and analysis of 2D photogrammetry among participants in the National Health and Morbidity Survey (NHMS) 2020, aged 18 years and above. The sample strategy was discussed in full in the NHMS 2020 report (11) and in our previously published study (10). In brief, the sampling frame for this study was based on the amended National Population and Housing Census 2020 by Department of Statistics Malaysia (DOSM)(12).…”
Section: Methodology Malaysia Anthropometric Databasementioning
confidence: 99%
“…It was showed that facial dimension difference existed between Australian-born, United Kingdom-born, and other foreign-born groups by an anthropometric survey of Australian Male [14] . Lim et al [15] found that there were signi cant differences in eight dimensions including bizygomatic breadth, minimum frontal breadth, bigonial breadth, menton-sellion length, interpupillary distance, head breadth, nose protrusion, nose breadth, nasal root breadth and subnasal-sellion length between birthplace and ethnicity in Malaysia. Statistically signi cant differences in facial anthropometric dimensions were noted between four racial/ethnic groups including Caucasian, African-Americans, Hispanic, and other (mainly Asian) in the USA [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Between December 2021 to January 2022, a total of 135 participants from the states of Selangor, Kuala Lumpur, Putrajaya, Melaka, and Negeri Sembilan were recruited to participate in this study. They were randomly selected from a subset of respondents from a previous study conducted in 2020 that collected facial anthropometry data among Malaysians [ 30 ]. Participants were selected based on their facial cells (cell 1–10) and sizes (small, medium, and large) based on the Malaysian bivariate facial panel derived from Malaysia’s facial anthropometry data [ 30 ], which was categorised by their facial length (menton-sellion length) and facial width (bizygomatic breadth) ( Fig 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Most FFR were imported from the US and China. Based on available studies, the US and China’s population have different facial dimensions and facial panels compared to Malaysians [ 30 , 31 ]. With the assumption that the produced FFR were based on their facial panels, the imported FFR will most likely unable to fit well with our population.…”
Section: Introductionmentioning
confidence: 99%